Kepercayaan Guru, Keadilan Organisasi Dan Perlakuan Inovatif Guru Di Sekolah Rendah - Mansor, Alina Mazwin (2015)
Kajian ini bertujuan untuk mengenal pasti pengaruh moderasi kepercayaan organisasi dan pemimpin terhadap hubungan antara keadilan organisasi dengan perlakuan inovatif guru di sekolah rendah. Sebanyak 480 orang guru dari 50 buah sekolah rendah di Pulau Pinang telah dipilih secara rawak sebagai sampel kajian. Satu set soal selidik yang terdiri daripada empat bahagian telah digunakan untuk memperoleh data daripada responden mengenai respon mereka ke atas keadilan organisasi, kepercayaan terhadap organisasi dan pemimpin, serta perlakuan inovatif guru. Soal selidik yang digunakan bagi memperoleh data adalah daripada Thiayagarajan (2011) bagi keadilan organisasi, Scott (1981) bagi kepercayaan terhadap organisasi dan pemimpin, serta Nik Azida (2007) bagi perlakuan inovatif guru. Dapatan menunjukkan hanya dimensi keadilan interpersonal mempunyai pengaruh yang signifikan terhadap kepercayaan organisasi. The purpose of this study is to understand the influence of leader’s trust and organizational trust on the relationship between organizational justice and innovative behavior among teachers in primary school. For the purpose of this study about 480 teachers from 50 primary schools in Penang has been choose randomly. In collecting the data a set of questionnaire comprising four main parts has been used to all the respondent in response to the organizational justice, leaders and organizational trust, and teacher’s innovative behavior. The data was collected through questionnaire in reference to Thiayagarajan (2011) for organizational justice, Scott (1981) for leaders and organizational trust, and Nik Azida (2007) for teacher’s innovative behavior. The result of these study showed that interpersonal justice is the only dimension that significantly influenced the organizational trust. Following, dimension of distributive justice, interpersonal justice, and informational justice significantly influenced the principal’s leadership trust. The results also showed that the organizational trust; informational justice significantly influenced the teacher’s innovative work behavior (new idea generation).